FACTORS AFFECTING FAMILY BEHAVIOR PATIENTS IN WASHING HANDS WITH SOAP (CTPS) AT HAMIDAH 1 AND HAMIDAH 2 CLINICS IN 2022 - Siti Fitri Amriana; Achmad Rifai (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Hand washing is an effective measure in preventing the spread of disease in the hospital area. Washing your hands with soap and water will kill 90% of the contaminants on your hands. The act of cleaning hands will reduce the incidence of healthcare-associated infections (HAIs). The purpose of this study was to determine the factors that influence the behavior of the patient's family in performing CTPS at the Hamidah 1 and Hamidah 2 Clinics in 2022. This study is a quantitative analytic study. The research design was cross sectional with a sample of 49 people in May 2022. The results of the study showed that there was an influence of knowledge, information media exposure and availability of facilities on the behavior of the patient's family in washing hands with soap with each p value of 0.003; 0.005; 0.004. This research is expected to provide knowledge for Health Workers who work in Hamidah I and Hamidah II Clinics as well as increase knowledge for people who visit Hamidah I and Hamidah II Clinics.